The influence of steam cleaning procedures on the surface roughness of commonly used type III dental stone for the fabrication of removable dentures. (8th February 2012) - Cilingir, Altug; Geckili, Onur; Parlar, Zeynep; Gencel, Burc; Bozdag, Ergun; Temiz, Vedat
Abstract : doi: 10.1111/j.1741‐2358.2012.00669.x The influence of steam cleaning procedures on the surface roughness of commonly used type III dental stone for the fabrication of removable dentures Objective: This study investigated the possible detrimental effects of steam treatment on the surface of type III dental stone, which is a common laboratory material used for the construction of removable dentures. Material and Methods: Forty dental stone specimens were prepared and divided into four groups (A, B, C and D), and group A was used as the control group. The other groups were treated with steam from a standard distance for varying durations (30, 60 and 120 s). Results: The duration of steam cleaning significantly increased Ra values ( F = 63.150, p = 0.000). Similarly, the duration of steam application was directly correlated with the weight changes ( F = 17.721, p = 0.000). A significant amount of dental stone can be removed from the surface while treating with steam. Conclusion: These studies demonstrated that expanded periods of steam cleaning cause weight loss and abrade the surface of type III dental stones; therefore, these devices should be used with caution during denture fabrication procedures.